A study of the wear damage on gas turbine blades. (March 2016) - Laguna-Camacho, J.R.; Villagrán-Villegas, L.Y.; Martínez-García, H.; Juárez-Morales, G.; Cruz-Orduña, M.I.; Vite-Torres, M.; Ríos-Velasco, L.; Hernández-Romero, I.
Abstract: In the present work, a study and description of the wear damage of the first-stage compressor blades of a gas turbine were conducted. The type of the equipment was a gas turbine Centaur 40 GT and the deterioration of the blades was after around 8000 h of service. This equipment is located in the City of Campeche in Mexico where the weather conditions are extremely warm. The gas turbine combines high performance operation with rugged industrial construction. This design provides high efficiency, low maintenance and a long service life. For power generation, the components that are on direct contact with air at different stages of operation are the compressor blades which are exposed to severe wear damage for the impact of particles, environmental contaminants such as salts, sands and sulphur. Due to this fact, the wear damage on the turbine blades was analysed. Firstly, a tribological characterization was conducted for obtaining the chemical composition of the turbine blades, which were in operation, by using energy dispersive X-ray analysis (EDS). Atomic Force Microscopy (AFM) was used to measure the roughness and has a perspective of the degradation of the surfaces of the blades after real service. Hardness tests were also conducted to determine the material that was employed to manufacture the blades. Additionally, optical microscopy and scanning electron microscopy (SEM) were used to identify the wear mechanisms on the surfaces. This allowed obtaining a more complete failure analysis. The wear modes were severe pitting action, large craters similar to those observed in solid particle erosion when the samples are impacted at normal incidence, corrosion and a few irregular scratches similar to ploughing action in abrasive wear. Highlights: A description of the wear mechanisms of blades of a gas turbine was performed. EDS analysis showed the chemical changes in different unworn and worn zones. Wear mechanisms were identified using optical and SEM images. AFM showed the surface degradation for each damaged zone, after real service.